PENERAPAN SISTEM LAYANAN PENGADUAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA SEMARANG - Dhiya Alhaq Surya Renaldhy; Dewi Rostyaningsih; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
In public services there are many types of review methods that can be carried out so that they work well or are in accordance with organizational goals. One of them is the implementation of e-government in the complaint service at the Semarang City Investment and One-Stop Service Office which was analyzed using management information system methods. The management information system describes the management process of an information system such as how the complaint service system is planned, designed, implemented and managed. Data collection methods used in this qualitative research are interviews, literature review and documentation. The results of the research on the Application of the Complaint Service System at the Investment and One-Stop Services Office (DPMPTSP) in Semarang City, namely the planning, design and implementation stages are going well while the management stage still requires improvement. Constraints encountered include the limitations of existing system functions and the public's lack of understanding in utilizing information systems.